Foundation HTML5 canvas - Hawkes, Rob (Apress, 2011)
Foundation HTML5 Canvas: For Games and Entertainment teaches you how to make exciting interactive games and applications using HTML5 canvas. Canvas lets you produce graphics, animations, and applications using the HTML5 and JavaScript web standards. It allows you to draw directly within the browser without the need for third-party plugins like Adobe Flash, and so canvas works perfectly across desktop and mobile devices, like the iPhone and Android. Foundation HTML5 Canvas begins by introducing you to HTML5 and the cool new features that it opens up for you. You are then offered a quick guide to JavaScript programming to get you up to speed. Next up you'll receive a thorough introduction to the canvas element, which teaches you how to draw objects within the browser with great ease. Once the basics are covered you?ll move on to the more advanced features of canvas, including image and video manipulation. You?ll also learn how to create realistic animations with the help of some basic physics. Foundation HTML5 Canvas then teaches you how to create two thrilling space-based games using all the skills you?ve learned so far. You'll find plenty of code examples and illustrations designed to help you understand even the most complex of topics. HTML5 is already here for you, and this book will provide you with all the information you need to enjoy the show. For more information, source code, and the latest blog posts from author Rob Hawkes, visit http://rawkes.com/foundationcanvas.